PENINGKATAN KETERAMPILAN BERBICARA MELALUI TEKNIK BERCERITA MAHASISWA TINGKAT 1 PROGRAM STUDI KEPERAWATAN STIKES SYEDZA SAINTIKA PADANG - Ayu Gustia Ningsih (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
Indonesian language learning is still applied with teacher centered learning in which the students face difficulty in asking questions. The students tend to be lazy to do their homework if they do not understand their materials. The lack of motivation and activities cause minimum of their assessment. This research is aimed at identifying the influence of story telling technique in increasing students learning outcome in Indonesian language course in nursery study program STIKes Syedza Saintika Padang. Based on the problem, the story telling technique is expected to increase students activities and their learning outcome. This research is classroom actions research and the subject of the research is 25 people of the first semester students of nursery study program STIKes Syedza Saintika Padang. The data is collected by using observation shheets and result tests. The technique of analyzing the data is descriptive and supported by the analysis of students learning outcome. This research is divided into 2 cycles and each of the cycles consist of 3 meetings. The result shows that cycle I mean is 65,55 and cycle II is 88,96. This shows that there is an increase of students acitivities. Moreover, it can be concluded that Indonesian language can be taught by using story telling technique in order to increase their activities and learning outcomes.Key Words: improving, speaking ability, story telling technique